Fenomena Orgen Tunggal Pada Tradisi Pernikahan di Desa Kasai Tinjauan Frugal Living dalam Perspektif Hadis - Oktavia, Abel; Uswatun Hasanah; Muhammad Ghazali (Jurnal Diskursus Islam, 2026)
Marriage in Islam emphasizes ease, simplicity, and blessing. However, in the social practice of Kasai Village, the tradition of orgen tunggal has shifted from optional entertainment to a socially obligatory, prestige-laden element of wedding ceremonies. This study aims to describe the practice, analyze its socio-economic impacts, and evaluate it through the perspective of the Prophet Muhammad’s hadith and the concept of frugal living in Islam. A qualitative descriptive approach was employed using sociological and hadith-normative frameworks. Data were collected through observation, documentation, and in-depth interviews, then analyzed thematically alongside takhrij and hadith commentary. The findings reveal that the institutionalization of orgen tunggal as a symbol of social legitimacy drives rising wedding costs, debt practices, asset pawning, and delayed marriage age. From the hadith perspective, this practice potentially contradicts the principles of simplicity and the prohibition of isrāf (excessiveness) and tabdzīr (wastefulness). The concept of frugal living is positioned as a contemporary ethical approach aligned with hadith values by promoting proportional financial management and long-term welfare. The novelty of this study lies in integrating sociological analysis of local tradition with hadith scholarship and frugal living as a practical ethical framework